ALS患者に生きる喜びを - 宮野 志津江; 新田 豊美 (The Journal of Showa Hospital, 2007)
According to 2002 Ministry of Health, Labour and Welfare investigation, Japan has 6,646 amyotro-phic lateral sclerosis (ALS) patients. It increases year by year. ALS patients are difficult to communicate be-cause their ability to speak and write deteriorates remarkably. An ALS patient in our hospital became difficult to communicate and began to be pessimistic. We talk with a patient through communication software "DEN-NO-SHIN". At the result. A flavor of a patient is stable. 平成14年厚生労働省調べによると、現在日本には6646人の筋萎縮性側策硬化症(ALS)患者がおり、年々増加傾向にある。ALSは発声能力や筆記能力が著しく低下するため、周囲の人とのコミュニケーションが難しくなることが多い。今回、コミュニケーションが困難で、悲観的発言が目立つようになってしまったALSの患者様に対し、『伝の心』というコミュニケーションツールを患者様が興味を持つように工夫し利用することで、メタコミュニケーションをとることが出来、患者の情緒を安定させることが出来た。